Do Female Representatives Adhere More Closely to Citizens' Preferences Than Male Representatives? - David Stadelmann; Marco Portmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2012)
We analyze whether female or male members of parliament adhere more closely to citizens' revealed preferences with quasi-experimental data. By matching individual representatives' voting behavior on legislative proposals with real referenda outcomes on the same issues, we identify the effect of gender on representatives' responsiveness to revealed preferences of the majority of voters. Overall, female members of parliament tend to adhere less to citizens' preferences than male parliamentarians. However, when party affiliation is controlled for, the effect of gender vanishes. These results are consistent with other evidence showing that women are more socially minded and tend to affiliate themselves more with left parties.
Keywords: D73; J16; J10; 330; Gender; Discrimination; Voter Preferences; Political Economy